Advance equitable livelihoods - Neufeld, Lynnette M.; Huang, Jikun; Badiane, Ousmane; Caron, Patrick; Forsse, Lisa Sennerby (Springer, 2023)
Food system transformation provides the opportunity to shift current trends in all forms of malnutrition, prioritizing the availability and affordability of nutritious food for all – from shifting priorities in agricultural production, to improved food systems that favor nutrition and sustainability. The task of Action Track 4 is to explore approaches to doing so that will advance equitable livelihoods for producers, businesses, workers across the food system and consumers, with a particular emphasis on addressing inequalities and power imbalances. As the Science Group for AT 4, we explore the nature of these issues, using the drivers of food systems as articulated by the High Level Panel of Experts of the UN Committee on World Food Security (HLPE 2020) as framing. Small and medium-sized producers and people who rely on food systems in rural and urban areas for livelihoods are disproportionately affected by all biophysical and environmental drivers, including soil and water resources and climate change. Unequal opportunity in access to all types of resources reduces overall production, resilience and rural transformation. Advances in innovation, technology and infrastructure have had important impacts on food production and sustainability, transportation and processing along food value chains, marketing, and, ultimately, diets, including the consumption of both nutritious and unhealthy foods. However, achievement of equitable livelihoods in food systems will require that issues of access to contextually suitable innovation and technology, inclusive of indigenous knowledge, be substantially enhanced. Many economic and political factors can be essential causes of inequality and power imbalances at the household, community, national and global levels, which may constrain the ability of food system transformation to deliver poverty reduction and sustainable, equitable livelihoods. Finally, vast evidence illustrates that several socio-cultural and demographic drivers underpin inequalities among and within societies and constrain the potential for some to benefit from actions to improve their livelihoods, particularly women, youths, the disabled, the elderly and indigenous peoples. These issues have been exacerbated by the COVID-19 pandemic. The pandemic is having a significant impact on global commodity markets and trading systems, economic growth, incomes, and poverty levels, with a likely disproportionate burden falling on vulnerable communities in both urban and rural areas. This is likely to worsen inequalities and set back progress against poverty and hunger goals. To address these issues, we must transform not only food systems, but the structures and systems that continue to enable and exacerbate inequities. Drivers of food system inequities are highly interconnected, and progress in addressing one will likely require change across several. For example, globalization and trade interact with other powerful drivers, especially technology resource mobilization and demographic trends, which shape food production, distribution, and consumption. Hence, in the final section, we reflect on several factors that should be part of effective solutions for combating inequalities in food systems, including rights-based approaches. We then share a series of recommendations aimed at enhancing inclusive decision-making, protecting the livelihoods of those living in situations of vulnerability while creating opportunities, adapting institutions and policies to favor equitable food system livelihoods, and increasing investment so as to realize the potential of improved institutional and policy actions. We invite governments, businesses, and organizations to hold themselves and others to account in advancing equitable livelihoods, and open avenues towards realizing the potential of science, innovation, technology, and evidence to favor equitable livelihoods.